STRATEGI PENINGKATAN KESEJAHTERAAN MUSTAHIK MELALUI PROGRAM KEMANDIRIAN UMAT OLEH LAZIZMU KOTA PEKANBARU - Nur Alhidayatillah; Risa Permata Sari (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2020)
Zakat collected by LAZISMU Pekanbaru is distributed through the Pemberdayaan Kemandirian Umat (PKU) program in the form of venture capital assistance, productive facilities, coaching, mentoring, and entrepreneurship training. This research was conducted to find out how the strategy of mustahiq welfare through the PKU program by LAZISMU Pekanbaru. The type of research was descriptive qualitative. The methods of data collection were observation, interviews, and documentation. This research involved 6 participants. The results of this research reveal that there are four forms of strategy undertaken to improve mustahiq welfare including; First, through venture capital in the form of giving a sum of cash to develop productive activities. Second, the provision of productive facilities such as tools to support the business developed by the mustahiq. Third, giving guidance on strengthening mustahiq worship and business through recitation and meetings and mentoring by visiting the mustahiq business directly by the PKU program staff. Fourth, the strategy is through entrepreneurship training.